(untitled) (Marketing Journal, 2025)
This article analyzes the need to develop an innovative management system in small businesses, the existing problems and ways to overcome them. Modern approaches to innovation management, the advantages of introducing digital technologies, as well as proposals aimed at improving the efficiency of management processes have been developed. Also, based on foreign experience, optimal models of innovative management in small businesses are considered and the prospects for their adaptation to national conditions are highlighted. The research results serve to modernize small businesses and ensure their competitiveness.